Application of the world health organization guidelines for the treatment of severely undernourished children - Bernal Parra, Carlos; Alcaraz López, Gloria Margarita; Giraldo Barrera, Victor H.; Lopera Marín, Jhon E.; Botero López, Jorge (Investigación y Educación en Enfermería, 2008)
Objective: Adaptation and application of the WHO protocol for the treatment of the severe undernourished children Materials and methods: This is a descriptive and prospective study. It was conducted during one year on 53 under- five severely undernourished children, i.e. weight / size below minus three standard deviations, or showing edemas. Some suffered it under the two criteria. The WHO criteria were applied. Results: 25 children (47.1%) suffered kwashiorkor, 24 (45,2%) wasting and 4 (7.5%) mixed undernourishment. The median age was 13.5 months (DE 11.8) The access associated morbility comprised acute and persistent diarrhea, pneumonia, dermopathies, sepsis, urinary infection and anemia. The median hospitalization was 21 days (DE 9,47). 35 children (66%) reached the target of minus one standard deviation in weight / size, 14 (26.7%) were discharged before reaching the targeted weight and 4 (7.3%) deceased. Discussion: in recent years severe malnutrition is back in Colombia and the treatment of these children is not rovided by the current social security system. The World Health Organization considers that undernourishment is associated with 60% of deaths in minors under five. In a first level hospital the application of the WHO protocol was successful. Other studies point satisfactory results with the application of the protocol. Key words: Nutritional disorders, dietotherapy, kwashiorkor, wasting.